An Inactivation Gate in the Selectivity Filter of KCNQ1 Potassium Channels - Gibor, Gilad (The Biophysical Society, 2007)
Inactivation is an inherent property of most voltage-gated K(+) channels. While fast N-type inactivation has been analyzed in biophysical and structural details, the mechanisms underlying slow inactivation are yet poorly understood. Here, we characterized a slow inactivation mechanism in various KCNQ1 pore mutants, including L273F, which hinders entry of external Ba(2+) to its deep site in the pore and traps it by slowing its egress. Kinetic studies, molecular modeling, and dynamics simulations suggest that this slow inactivation involves conformational changes that converge to the outer carbonyl ring of the selectivity filter, where the backbone becomes less flexible. This mechanism involves acceleration of inactivation kinetics and enhancement of Ba(2+) trapping at elevated external K(+) concentrations. Hence, KCNQ1 slow inactivation considerably differs from C-type inactivation where vacation of K(+) from the filter was invoked. We suggest that trapping of K(+) at s(1) due to filter rigidity and hindrance of the dehydration-resolvation transition underlie the slow inactivation of KCNQ1 pore mutants.